A multifunctional contrast dye for morphological research. Issue 2 (8th January 2016) - Xia, Qian; Feng, Yuanbo; Yin, Ting; Liu, Yewei; Liang, Sayuan; Liu, Jianjun; Tong, Linjun; Huang, Gang; Yu, Jie; Jiang, Yansheng; Himmelreich, Uwe; Oyen, Raymond; et al.
ABSTRACT: Objectives: We sought to devise and test a multifunctional contrast dye agent for X‐ray based digital radiography (DR) or computer tomography (CT), magnetic resonance imaging (MRI), and colored staining in ex vivo validation part of animal experiments. Materials and Methods: The custom‐formulated contrast dye namely red iodized oil (RIO) was prepared by solubilizing a lipophilic dye Oil Red O in iodized poppy seed oil (Lipiodol or LPD) followed by physicochemical characterizations. To explore and test the utility of RIO, normal rats ( n  = 10) and rabbits ( n  = 10) with myocardial infarction (MI) were euthanized by overdose of pentobarbital for infusion of RIO through catheterization. The bodies and/or excised organs including heart, liver, spleen, kidneys, pancreas, and intestines of the rats and rabbits were imaged at clinical mammography, CT and MRI units. These images were qualitatively studied and quantitatively analyzed using Wilcoxon Rank test with a P value < 0.05 being considered of a statistically significant difference. Imaging findings were verified by histomorphology. Results : All experimental procedures were carried out successfully with the use of RIO. T1 and T2 relaxation time was 234.2 ± 2.6 ms and 141.9 ± 3.0 ms for RIO, close to that of native LPD. Proton ( 1 H) NMR spectroscopy revealed almost identical profiles between RIO and native LPD. The clinical mammography unit, 128‐slice CT scanner and 3.0T MRI magnet were well adapted for the animal experiments. Combined use of RIO with DR, MRI, CT and histology enabled microangiography of the organs, 3D visualization of rat pancreas, validation of in vivo cardiac quantification of MI and cause determination of the rabbit death after coronary occlusion. RIO appeared as red droplets and vacuoles in vessels by frozen and paraffin sections. Image analysis showed the superiority of DR images, which provided better overall image quality (4.35 ± 0.49) for all analyzed liver vessel segments. MRI images revealed moderate to good overall image quality ratings (3.45 ± 0.52). Comparing the signal intensities of vessel and liver with different MRI sequences, all P values were <0.01. Conclusions: RIO proved to be a multifunctional contrast dye, which could be applied as an imaging biomarker for tissue vascularity or blood perfusion, for visualization of organ anatomy and for ex vivo validation of in vivo animal experiments. Microsc. Res. Tech. 79:111–121, 2016 . © 2016 Wiley Periodicals, Inc.